How the Implementation of the Industrial Revolution 4.0 Management Information System Influenced Innovation: The Case of Small and Medium Enterprises in Indonesia - Hertati, Lesi; Syafarudin, Afriapollo (Journal of Asian Business Strategy, 2019)
Management Information System is a planning system in an organization that involves management of internal controls such as the use of resources, documents, technology, and management accounting as one of the strategies in business. Management information systems in the business or corporate world aim to collect, process, store and analyze information and then disseminate it for specific purposes. Management information systems function as a reference for decision making in an organization or company and management functions are applied in business. The difference in information requirements will lead to different data that must be entered and the management information system format used. Reality states that many management information systems in various government and private institutions have various problems including integration issues, ease of use, ease of access, ease of adaptation to changing conditions and the ability to produce management information as needed. The purpose of this study was to determine how much the application of the industrial revolution 4.0 management information system influenced innovation. This method is a descriptive and verification method, the analytical tool is structural equation modeling (SEM, Lisrel). The results showed that innovation affected the implementation of the industrial revolution 4.0 management information system.